Effect of alumina/gnp hybrid nanoreinforcement on wetting and mechanical properties of adhesively bonded aluminium alloy with epoxy - Mohamad Syaiful Izwan, Alies (2024)
Hybrid nanoparticle reinforcement has demonstrated a significant increment in bonding strength compared to polymer composites with a single nano reinforcement. However, experimental results are rather limited and investigation regarding the parametric effects of nano-reinforcement weight content and weight ratio combinations on the joining strength of adhesive joining not yet been discussed comprehensively. To date, the effects of Alumina/GNP hybrid nano reinforcement on wetting behavior, tensile properties and fracture behavior have been studied. The correlation of that properties was studied as well. In current study, epoxy adhesive modified with various nanoparticle content (0.5, 1.0, 1.5 and 2.0 wt%) and various weight ratio combination (10:0, 7:3, 5:5, 3:7 and 0:10 Alumina:GNP) have been fabricated into ASTM E8 and ASTM D1002 specimens. For the tensile strength of the ASTM E8 specimen, the highest improvement (64.75%) was demonstrated at 1.5 wt% loading, with the strongest correlation (R=0.52) between GNP ratio and tensile strength. Meanwhile, for fracture elongation, the maximum increment (130.77%) was observed at 1.5 wt% loading, with the correlation value of R=0.65 between alumina weight ratio and fracture elongation. In lap shear joints, the highest increases in strength and fracture elongation occurred with 1.5 wt% hybrid nanoreinforcement content with increment up to 15.13% and 10.53% respectively as compared to specimen with unmodified adhesive. Correlations were strongest at this loading for both strength (R=0.89) and elongation (R=0.78). Up to 1.5wt%, increased of alumina weight ratio improved wettability, with spread area rising by 309%. The effect was most pronounced at 0.5 wt%. At 1.5 wt% loading, failure mechanisms showed optimal synergistic interactions between alumina and GNP nanoparticles. A positive relationship between shear strength and spread area was noted at higher loadings, with the best correlation at 2.0 wt%. However, property improvements peaked at 1.0wt%. In summary, the adhesive with 1.5 wt% Alumina/GNP hybrid nanoparticle reinforcement demonstrated the optimal balance of enhanced tensile properties, shear strength, fracture elongation, wettability, and failure interactions. While 2.0 wt% exhibited good property-wettability correlations, the overall improvements were marginal beyond 1.0 wt% loading of alumina/GNP hybrid nanoreinforcement. Therefore, 1.0 wt% alumina/GNP hybrid nanoreinforcement seems to be the optimal hybrid nanoparticle concentration and 7:3 weight ratio combination of Alumina/GNP hybrid nano reinforcement